Boron-Induced Suppression of Recrystallization during Creep in FeNi-Based Superalloys: Insights from Grain Boundary APT Analysis - Lee, Ji Yeong; Cham Il Kim; Do Hyang Kim; Kim, Yanghee; Jeong, Young Woo; Kim, Hae Ryoung; Yu, Byung Yong; Ahn, Jae Pyoung (2025 한국표면분석학회 제4회 종합학술대회, 2025)
FeNi-based superalloys are commonly used in turbine blades of aircraft engines and other hightemperature load-bearing components. These alloys offer a significant cost advantage compared with Niand Co-based superalloys. Numerous studies have investigated recrystallization during high-temperature deformation or creep in superalloys. It is well known that the addition of boron to superalloys improves creep life, rupture strength, and tensile ductility at elevated temperatures. While recrystallization during creep has been extensively studied, the effect of boron addition on this process has not been examined in detail. This study investigates the effects of boron on microstructural evolution and creep properties in FeNi-based superalloys, demonstrating that boron plays a key role in significantly enhancing creep resistance by suppressing recrystallization during creep. The microstructures after creep rupture were observed using SEM. It was found that the crack tips in both alloys propagated along the grain boundaries during creep. The distribution of elements, including boron, was examined using atom probe tomography (APT). Correlative analysis combining TEM and APT was performed to confirm the grain boundaries. Such boron segregation is attributed to the strengthening mechanism, as confirmed by APT analysis.